ANALYSIS OF THE PROGRAM TO ACCELERATE STUNTING REDUCTION IN PIDIE DISTRICT IN 2022 - Iskandar; Syaukani; Muhammad Yani; Aripin Ahmad (PT. Radja Intercontinental Publishing, 2024)
For the prevention and handling of stunting, in 2019 the Aceh government designated 3 districts as stunting Focus Locations (Lokus), one of which is Pidie. To accelerate the reduction of stunting, the government set program indicator targets that must be achieved by 2024, especially in the stunting focus areas. The achievement of these indicators is a reflection of the performance of each district/city. To find out the description of the performance achievement of each indicator, it is measured by an index value approach. The study was conducted quantitatively; analyzing secondary data from 29 program coverage indicators divided into 6 dimension groups. Each dimension of the index has equal weighting. Index assessment by comparing the annual program coverage indicator value with the target value set nationally. The stunting index in Pidie stands at 51.6. Out of the six evaluated dimensions, family assistance and food security scored the lowest, with values of 39.0 and 18.0. In contrast, the nutrition dimension recorded a higher score of 71.7. The health dimension, along with social protection (63.7) and decent housing (53.1), also needs more attention from the local authorities, as the efforts in these areas to tackle stunting are still lacking. Nutrition has become a primary focus in Pidie's stunting prevention strategies, as evidenced by high iron tablet intake among adolescent girls (79.9) and pregnant women (94.11), good rates of complementary feeding (MP-ASI) for children aged 6-23 months (89.3), growth monitoring (83.7), and supplementary feeding programs (PMT) for pregnant women (72.3) and undernourished toddlers (77.1). However, exclusive breastfeeding (64.7) and iron tablet consumption among prospective brides (34.6) are areas with lower achievement. The nutrition dimension, with the highest index score, is expected to play a significant role in reducing stunting rates